Urban Poverty in Vietnam - Determinants and Policy Implications - Nguyen, Viet Cuong (2016)
This study examines the profile and determinants of poverty in the two largest cities in Vietnam – Hanoi and Ho Chi Minh. Data used in this study are from the 2009 Urban Poverty Survey. Using the poverty line of 12,000 thousand VND, year, the poverty incidence is estimated at 17.4 percent for Hanoi and 12.5 percent for Ho Chi Minh city.